ANALISIS KONSEP STRATEGI PEMASARAN PRODUK - Fadiyah Putri Nur Habibah; Rahmi Mutiara Azzury (Cahaya Ilmu Bangsa, 2024)
The aim of this research is to explore and explain relevant product marketing concepts and theories using a qualitative approach based on literature reviews. This research aims to understand how marketing strategies work in different contexts and the practices that companies have adopted in promoting their products. This study provides evidence that an effective marketing strategy must take into account factors such as a thorough analysis of market needs, the selection of appropriate distribution channels and the use of sophisticated communication techniques. However, this publication recognises the need for a deeper understanding of the market and digital evolution in order to develop more dynamic and relevant marketing strategies. This study considers that the existing literature is useful in providing guidance on how to develop marketing strategies to increase product competitiveness in international markets.